2019
DOI: 10.35333/jrp.2019.81
|View full text |Cite
|
Sign up to set email alerts
|

The role of the clinical pharmacist in patient education and monitoring of patients under warfarin treatment

Abstract: This study was carried out on patients who were under anticoagulation treatment with warfarin, at the outpatient cardiology clinic. The aim was to determine the effectiveness of pharmacist consultation, education, and intervention on each patient's therapeutic results. A cross-sectional randomized trial has been done. Twenty-five patients were included in the study. The Oral Anticoagulation Knowledge (OAK) Test, Short Form-36 (SF-36) and Duke Anticoagulation Satisfaction Scale (DASS) were applied. Patients res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…As anticoagulants are one of the leading causes of drug related adverse events and are considered high alert medications ( Shehab et al, 2016 ), additional measures should be considered to ensure safe utilization of these medications. It has been reported that pharmacists play an important role in the dosing, monitoring, and education of anticoagulation therapy ( Izzettin et al, 2019 ). A Saudi-based study concluded that implementation of the pharmacist-managed anticoagulation clinic had a positive impact on patient care ( Dib et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…As anticoagulants are one of the leading causes of drug related adverse events and are considered high alert medications ( Shehab et al, 2016 ), additional measures should be considered to ensure safe utilization of these medications. It has been reported that pharmacists play an important role in the dosing, monitoring, and education of anticoagulation therapy ( Izzettin et al, 2019 ). A Saudi-based study concluded that implementation of the pharmacist-managed anticoagulation clinic had a positive impact on patient care ( Dib et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, pharmacist interventions within warfarin management process, through counseling and education, were found to create good outcomes in patients' quality of life, treatment satisfaction, and level of awareness regarding their treatment, as well as better therapeutic outcomes and reduced risk of complications. 8 The objectives of the study are to evaluate the pharmacological knowledge about warfarin among community and hospital pharmacists in UAE, to evaluate the appropriate counseling practices of warfarin among community and hospital pharmacists in UAE, and to compare between community and hospital pharmacists regarding knowledge and counseling practices of warfarin in UAE.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, pharmacist interventions within warfarin management process, through counseling and education, were found to create good outcomes in patients’ quality of life, treatment satisfaction, and level of awareness regarding their treatment, as well as better therapeutic outcomes and reduced risk of complications. 8 …”
Section: Introductionmentioning
confidence: 99%